Gdańsk Ulica Grunwaldzka / wg fot. Jerzego Wendołowskiego. - Wendołowski, Jerzy (1913-1988) (Biuro Wydawnicze "RUCH", 1970)
Przedstawia fragment ul. Grunwaldzkiej w Gdańsku-Wrzeszczu, kamienice nr 53-33, ok. 1975 r.